Commercialization of Academic Research: Assessing the Enabling Conditions for German Universities - Odei, Samuel Amponsah (Academic Conferences and Publishing International, 2017)
Universities are multifaceted institutions actively playing an engaging role in society. Besides being built around education and research, universities in recent times have a new role which involves the commercialization of academic research. The Federal Republic of Germany has been successful with the commercialization of academic research and has been able to establish numerous spinoff firms through the initiatives of its numerous entrepreneurial universities. This paper seeks to assess the extent to which German universities are commercializing their academic activities and collaborating with industry through the creation of spin offs. The research employed the linear regression analysis to reach the aim of this research. The test and the pattern of statistical significance and the results of the regression coefficients indicate that the availability of funding for universities’ research commercialization has a positive effect on patent acquisition which is a vital component for the commercialization of academic research process in Germany.
Komercializace akademického výzkumu: hodnocení vhodnosti podmínek pro německé univerzity
Keywords: entrepreneur university; spinoffs; Germany; universities; commercialization of academic research; funding; patents; academic research; podnikatelská univerzita; spin-off; Německo; univerzita